The measurement of firm ownership and its effect on managerial pay - Jeremy S. S. Edwards; Wolfgang Eggert; Alfons J. Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper uses German evidence to address two questions about corporate governance. The effects of ownership on corporate governance have received much recent attention, but very little of this has been devoted to the appropriate way to measure firm ownership. The results of this paper show that the conclusions reached about the effects of ownership on corporate governance can depend critically on the particular ownership measure used, and that the widely-used weakest-link principle is wholly unsatisfactory as a means of dealing with the issues raised by pyramid ownership structures. The paper also shows that greater ownership concentration typically weakens the link between managerial pay and firm profitability. This is inconsistent with the hypothesis, emphasised in the recent literature on the USA, that large owners are a complement to, rather than a substitute for, such a link.
Keywords: G32; L25; M52; 330